Ownership structure and cash holding: A theoretical review - Rehan Zahid (Privietlab, 2026)
This study provides insights into how different types of ownership structures influence cash holdings. The PRISMA model was utilized in this study. Major theories, including the cash flow theory, were identified in this study. The literature was also studied to extract information on the variables used in this study. The literature suggests that managerial, family, government, and foreign ownership are positively associated with cash holdings, and institutional ownership is negatively associated with firms' cash holdings. The positive association between managerial ownership and cash holdings reduces agency costs and minimizes agency problems between managers and shareholders. Family ownership is positively associated with cash holdings because family owners retain cash to mitigate risks and ensure long-term survival. The inverse relationship between institutional ownership and cash holdings indicates that institutional owners are reluctant to share control rights with other stakeholders. These results are useful for financial experts, management, academicians, economists, auditors, and all firms' stakeholders.